Bis(1,10-phenanthroline-κ2 N,N′)(sulfato-κO) copper(II) ethanol monosolvate - Natthaya Meundaeng (2018)
The crystal structure of the title compound, [Cu(SO4)(C12H8N2)2] ·C2H5OH, arises from the assembly of the neutral complex [Cu(SO4)(C12H8N2)2] and an ethanol solvent molecule. The CuII ion is five-coordinate, surrounded by two pairs of N atoms from two independent N,N′-chelating 1,10-phenanthroline ligands, and one O atom of monodentate sulfate ligand, in a distorted trigonal-bipyramidal fashion. Spatial orientation of the ligands and the assembly in the solid state are stabilized by the C - H⋯O hydrogen-bonding interactions, established between the O atoms (from the sulfate ligand and the ethanol molecule) and the neighbouring 1,10-phenanthroline molecules. There is also an offset face-to-face π-π stacking between the 1,10-phenanthroline ligands. The ethanol solvent molecule is disordered over two orientations in the ratio 0.663 (10):0.337 (10). The crystal examined was subject to racemic twinning and the refined twin fraction was 0.346 (19).